Respuesta :
Answer:
-1√5-3√5=(√5)(-1-3)=(√5)(-4)=-4√5
Step-by-step explanation:
if you combine the radicals, you will receive the answer that is shown above.
Answer:
[tex]-4\sqrt{5}[/tex]
Step-by-step explanation:
Given expression: (square root 5) - (3 square root 5)
- ⇒ [tex]-\sqrt{5} - 3\sqrt{5}[/tex]
Since we have √5 common in both terms, let's factor √5.
- ⇒ [tex]\sqrt{5} - 3\sqrt{5}[/tex]
- ⇒ [tex]\sqrt{5} \times (-1 - 3)[/tex]
Finally, we can simplify;
- ⇒ [tex]\sqrt{5} \times (-4)[/tex]
- ⇒ [tex]-4\sqrt{5}[/tex]
Therefore, the combined radical of (square root 5) - (3 square root 5) is [tex]-4\sqrt{5}[/tex]